Reducing the risks of nuclear war - the role of health professionals - Abbasi, Kamran; Ali, Parveen; Barbour, Virginia; Bibbins-Domingo, Kirsten; GM Olde Rikkert, Marcel; Hanines, Andy; Helfand, Ira; Horton, Richard; Marsh, Bob; Mitra, Arun; Monteiro, Carlos; Naumova, Elena N.; et al. (Orapuh Journal, 2023)
Any use of nuclear weapons would be catastrophic for humanity. Even a “limited” nuclear war involving only 250 of the 13 000 nuclear weapons in the world could kill 120 million people outright and cause global climate disruption leading to a nuclear famine, putting 2 billion people at risk. We now call on health professional associations to inform their members worldwide about the threat to human survival and to join with the IPPNW to support efforts to reduce the near-term risks of nuclear war.